2020
DOI: 10.1007/s13201-020-1141-3
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and isotherm modeling for acid blue 113 dye adsorption onto low-cost nutraceutical industrial fenugreek seed spent

Abstract: The present study reports about the use of fenugreek seed spent as a new and efficient biosorbent for the removal of acid blue 113 dye from aqueous media and textile industrial effluent. The spent is a low-cost by-product of nutraceutical industry. The effects of various process parameters of adsorption, such as pH, initial dye concentration, adsorbent dose, adsorbent particle size, contact time and temperature onto nutraceutical industrial fenugreek seed spent (NIFGS) have been studied. Four numbers of two-pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…Comparing the Freundlich isotherm parameter k F determined in BB3-C/SiO 2 and BY2-C/SiO 2 systems with the linear (29.32-243.99 mg 1−1/n L 1/n /g) and non-linear (27.37-223.25 mg 1−1/n L 1/n /g) regression, it was found that these values are close to each other. Tables 2 and 3 show that 1/n heterogeneity factors are below 1 which means a favorable adsorption of a physical nature during the basic dye adsorption on the composite (e.g., hydrogen bonds between N atoms of the dyes and -OH or -OH 2 + groups present on composite surface) [42,43]. The Marquardt's percent standard deviation values varied from 0.032 to 0.365 and were the smallest precisely for the Freundlich model.…”
Section: Isotherm Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing the Freundlich isotherm parameter k F determined in BB3-C/SiO 2 and BY2-C/SiO 2 systems with the linear (29.32-243.99 mg 1−1/n L 1/n /g) and non-linear (27.37-223.25 mg 1−1/n L 1/n /g) regression, it was found that these values are close to each other. Tables 2 and 3 show that 1/n heterogeneity factors are below 1 which means a favorable adsorption of a physical nature during the basic dye adsorption on the composite (e.g., hydrogen bonds between N atoms of the dyes and -OH or -OH 2 + groups present on composite surface) [42,43]. The Marquardt's percent standard deviation values varied from 0.032 to 0.365 and were the smallest precisely for the Freundlich model.…”
Section: Isotherm Studiesmentioning
confidence: 99%
“…They are present in wastewater together with dyes and affect the efficiency of their removal, often being a threat to aquatic ecosystems themselves. It was stated that all anionic surfactants are classified harmful for LC 50 between 10-100 mg/L while non-ionic surfactants are toxic for LC 50 between 1.0 and 10 mg/L [42][43][44]. Therefore, the important aspect of the paper was to investigate the dyes removal by the composite from the solutions containing 0.25 g/L of surfactants.…”
Section: Phase Contact Time and Surfactant Impact On Basic Dye Adsorptionmentioning
confidence: 99%
“…An experimental design [26] for optimizing five process parameters at two levels, as mentioned in Table 1, was prepared for the BG-HNT system to obtain a quadratic regression equation using the ANOVA model. 2a,b.…”
Section: Statistical Optimization Of the Process Parametersmentioning
confidence: 99%
“…Response DB15-HNT = 42.1 + 18.5 × A − 6.2 × B + 19.5 × C − 32.0 × D − 13.4 × E − 3.4 × AB + 11.8 × AC − 3.0 × BC − 19.8 × A 2 + 1.6 × B 2 − 27.5 × C 2 + 24.2 × D 2 + 23.4 × E 2 (1) The regression coefficient [51][52][53][54][55][56][57][58][59][60][61][62][63] indicates the effect of various features affecting the adsorption capacity on the adsorption capacity [64][65][66][67]. The surface and contour plots represented in Figure 14 show the combined effect of two features on the process of adsorption.…”
Section: Statistical Process Optimizationmentioning
confidence: 99%